A High‐Performance Room‐Temperature Li||Ga–Sn Liquid Metal Battery for Grid Energy Storage. Issue 9 (1st July 2021) - Wang, Kaizhao; Hu, Jin; Chen, Tianyou; Tang, Jingtao; Wang, Zhiyi; Fan, Ningning; Zhang, Weijun; Wang, Kaijun
Abstract : Herein, a room‐temperature liquid metal battery (LMB) with a solid lithium anode electrode and gallium–tin (Ga–Sn) alloy cathode electrode is reported. With the improved wettability of the electric collector and grain‐refined liquid metal droplets cathode, the aforementioned LMB exhibits good cyclic reversibility and negligible self‐discharge. The result shows that the assembled Li||Ga–Sn battery has a satisfactory specific capacity (409 mAh g −1 ) and high energy efficiency (up to 92%). The low melting point Ga–Sn alloy can construct fast kinetics for the redox reaction and improve the electrode reaction kinetics, imparting the Li||Ga–Sn system with high discharge voltage (0.77 V at 1C) and smaller polarization voltage at different current densities, which ensure the high Coulomb efficiency and good rate performance of the battery. Moreover, the battery stably cycles at 35 °C for 60 cycles at the 1C rate, with no significant capacity degradation. With good electrochemical performance, simple structure, easy maintenance, and high safety, this room‐temperature Li||Ga–Sn battery may be a promising choice for power grid energy storage applications. Abstract : A room‐temperature liquid metal battery with a solid lithium anode electrode and gallium–tin (Ga–Sn) alloy cathode electrode is reported. The Li||Ga–Sn battery has fast reaction kinetics, a satisfactory specific capacity, high energy efficiency, good rate performance, and stable cyclic reversibility, which is a promising choice for power grid energy storage applications.